EMPIRICAL RESEARCH IN BEHAVIORAL ECONOMICS - MARCHYSHYN, Nazar (Scientific journal «World of Finance», 2024)
Introduction. The modern economic world, saturated with instability and uncertainty, requires new approaches to understanding and managing economic processes. In this context the relevance of experimental behavioral economics research is extremely important. Making economic decisions is not an exclusively rational process, because it is also connected with psychological factors that determine the behavior of subjects in the market and in management processes. Understanding these psychological aspects, their influence on decision-making and the development of strategies that would take these features into account become a key task in the conditions of the modern global economic environment. The relevance of the study of experimental behavioral economics covers not only practical application in various strategies and management decisions, but is also considered in the context of the formation of socially responsible economic policies and interaction between various market subjects. Research in this direction will contribute to the formation of more flexible and adaptive strategies aimed at achieving sustainable development in conditions of uncertainty and rapid changes. The purpose of the article is to highlight the key aspects of experimental behavioral economics, to reveal its essence and the importance of its application in the modern economic environment, ta analyse the psychological factors, that influence economic decision-making, and to determine the importance of experimental behavioral economics as a tool for management and development of modern economic strategies. Results. The general results of the study indicate the need to rethink traditional approaches in the modern economy and demonstrate the significance and practical value of experimental behavioral economics in the development and optimization of strategies in various spheres of modern society. Conclusions. The analysis of the conclusions, presented in the article, opens up new perspectives for further research in the context of the development of the theory of behavioral economics and its impact on economic practice.